MORTGAGE HOUSING: THE CONCEPT, NATURE, GROUNDS OF ORIGIN - Майданик, Р. А. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2008)
The article deals with the grounds for the emergence of a mortgage and the content of the mortgage as a substantive law.